Best site for embryo transfer: the upper or lower half of endometrial cavity? - Franco, J. G.; Martins, AMVC; Baruffi, RLR; Mauri, A. L.; Petersen, C. G.; Felipe, V; Contart, P.; Pontes, Anaglória [UNESP]; Oliveira, JBA (Oxford University Press, 2004)
BACKGROUND: the objective of the present study was to determine the importance of the site of embryo transfer (upper or lower half endometrial cavity) on implantation and clinical pregnancy rates. METHODS: A total of 400 transfers guided by ultrasound were randomly assigned to two groups according to the distance between the uterine fundus and the catheter tip at the time of embryo placement. Group I (n=200) consisted of transfers corresponding to a distance of <50% of the endometrial cavity length (ECL), i.e. transfer in upper half of the cavity; and group II (n=200) consisted of transfers corresponding to a distance of greater than or equal to50%, of the ECL, i.e. transfer in lower half of cavity. The Student's t-test, Mann-Whitney test and Fisher's exact test were used where appropriate. RESULTS: the general characteristics of the study population and the main transfer cycle characteristics had an equal distribution (P>0.05) between groups I and II. No significant difference in implantation or pregnancy rates was observed between groups I and II. CONCLUSION: the implantation or pregnancy rates were similar whether the embryos were deposited in the upper or lower half of the endometrial cavity.
Keywords: embryo transfer; endometrial cavity length; implantation rates; IVF; pregnancy rates